2012
DOI: 10.4103/0019-5154.96193
|View full text |Cite
|
Sign up to set email alerts
|

Mucocutaneous and demographic features of systemic sclerosis: A profile of 46 patients from Eastern India

Abstract: Background:Systemic sclerosis (SSc) is a multisystem connective tissue disorder of uncertain etiology. The clinical picture is frequently dominated by prominent cutaneous manifestations that have diagnostic and prognostic significance. The objective of the present study was to find out the demographic profile and the relative frequencies and characteristics of different mucocutaneous features of SSc in a group of patients from eastern India. In addition, we sought to compare the frequency and pattern of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
11
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 8 publications
9
11
2
Order By: Relevance
“…17,18,[21][22][23][24] Cutaneous sclerosis was found in most patients in the present study and similar findings have been reported by other authors (range: 90-98.5%). [21][22][23][24] Fingertip ulceration was noted in 48% of patients which was also similar to that of previous studies (range: 37-63%). 18,21,22 In this study, "salt and pepper" pigmentation was seen in 44% of patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…17,18,[21][22][23][24] Cutaneous sclerosis was found in most patients in the present study and similar findings have been reported by other authors (range: 90-98.5%). [21][22][23][24] Fingertip ulceration was noted in 48% of patients which was also similar to that of previous studies (range: 37-63%). 18,21,22 In this study, "salt and pepper" pigmentation was seen in 44% of patients.…”
Section: Discussionsupporting
confidence: 92%
“…In a study conducted in Eastern India, 9 out of 46 patients were children. 21 Raynaud's phenomenon was seen in all patients of SSc and majority had sclerodactyly (76%) which was similar to studies from different parts of India. 17,18,[21][22][23][24] Cutaneous sclerosis was found in most patients in the present study and similar findings have been reported by other authors (range: 90-98.5%).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In SS, we found hidebound skin and decrease mouth opening in all patients followed by Raynaud's phenomenon (90%) and sclerodactyly (70%) similarly noted in study of Sudip Ghosh in eastern India. 12 In MCTD cases, all had given history of muscle weakness and pain followed by history of hair loss, joint pain and Raynaud's phenomenon (Image 6, 7).…”
Section: Diseasementioning
confidence: 99%